Elucidating ammonia's impact on non-gray radiation and thermometry during biomass co-firing via spectral guidance - Liu Huixin; Wang Chunbo; Sun Cen; Yu Xuewu; Zhang Xiaotian (Fuel Processing Technology, 2025)
Ammonia co-firing with biomass is a vital strategy for decarbonizing power generation, yet optimizing its efficiency and emissions necessitates accurate flame temperature monitoring. Reliable diagnosis, however, is impeded by strong, phase-dependent non-gray radiation from biomass (volatile vs. char) and the critically unquantified impact of NH3 on essential spectral radiative properties. This work systematically investigates the influence of NH3 concentration on the spectral emissivity ε(λ) of burning rice husk particles within the visible spectrum (400–700 nm) during distinct volatile and char combustion phases, utilizing simultaneous spectroscopy and RGB pyrometry. The investigation revealed that NH3 significantly lowers ε(λ) for both volatile combustion, where ελ decreases with wavelength (ε(λ) < 0.16), and char combustion, where ελ increases with wavelength (ε(λ) ≈ 0.35–0.75). Consequently, the key emissivity ratio εg/εr (at 530/600 nm) required for RGB pyrometry exhibited opposite behaviors: for volatile combustion, εg/εr > 1 and increased with NH3 concentration, whereas for char combustion, εg/εr < 1 and decreased with NH3 concentration. Building upon these quantitative findings, the developed and validated spectrally-guided RGB pyrometry methodology successfully corrects the substantial temperature overestimation inherent in the gray-body assumption, an error particularly pronounced at higher NH3 concentrations. This work yields both fundamental quantitative data on ammonia's impact on biomass non-gray radiation and a robust spectrally-guided diagnostic method, providing essential data and techniques for enabling accurate modeling, optimization, and control of biomass-ammonia co-firing processes.